Pengembangan Bahan Ajar E-Handout Berbasis Kodular untuk Sekolah Dasar Fase C pada Mata Pelajaran Bahasa Indonesia - Latip, Asep Ediana; Putri, Kinanti Adlina; Hokiani, Friski (Indonesian Journal of Elementary Education and Teaching Innovation, 2024)
This study aims to determine the validity and feasibility of products in the form of codular-based e-handouts that are usable, valid, practical, and effective in understanding Indonesian language subjects in phase C. This research is included in the Research and Development (R&D) development model in the form of ADDIE which consists of five stages of development namely analysis, design, development, implementation, and evaluation. The subjects in this study were instrument validators. All results of data analysis using the validity index assessment aspects of Aiken. With the results of data analysis in the aspect of validity obtained from the material expert test of 3 statements with a validity index value status of 0.5, 3 statements with a validity index status of 0.75, and 1 statement with a validity index value status of 1.00. Based on the validity index criteria from Aiken's validity of the design expert's score, the 3 value statements are included in the revision criteria, and 4 statements are in the valid criteria. According to the accumulation of assessments from design expert validators, it shows that this Kodular-based e-handout teaching material is suitable for use in learning with some notes that must be revised. The calculation results obtained from design experts based on the validity index from Aiken are 2 statements with a validity index value status of 0.5, and 5 statements with a validity index status of 0.75. Based on the validity index criteria from Aiken, the validity of the linguist's score, the 2 statements are included in the revision criteria, and 5 statements are in the valid criteria. It can be concluded that the development of codular-based e-handot teaching materials is valid and feasible to use for Indonesian language subjects in phase C.Keyword: teaching materials, codular, indonesian language